2012
DOI: 10.1016/j.jcma.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime-impregnated cement and systemic cefazolin for 1 week in primary total knee arthroplasty: An evaluation of 2700 knees

Abstract: Comparable with other measurements, cefuroxime-impregnated cement, accompany by systemic cefazolin for 1 week was shown to control postoperative deep infection to 0.19% (after primary TKA was performed in an operative setting without lamina flow and body exhaust suit).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In all studies there were no reports of toxicity or allergies attributed to the use of ALBCs. In addition, the bibliographic research was limited to published comparative studies (ALBC vs PBC) and did not take into account RCTs, RE studies and PRO trials in which there was no control group [5, 9, 18, 22, 27]. Thus, the conclusions of the present review are not absolute.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies there were no reports of toxicity or allergies attributed to the use of ALBCs. In addition, the bibliographic research was limited to published comparative studies (ALBC vs PBC) and did not take into account RCTs, RE studies and PRO trials in which there was no control group [5, 9, 18, 22, 27]. Thus, the conclusions of the present review are not absolute.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of surgeons use ALBC in primary TKR in the UK [100], Sweden [101], and Norway [99]. The use of ALBC in knee replacements reduces the percentage of prosthetic infection compared to bone cements lacking antibiotics [102,103].…”
Section: Prophylaxismentioning
confidence: 99%
“…Several reports showed that pre‐soaking of the graft in vancomycin solution was effective for the prevention of bacterial infection, but those surgeries did not use artificial materials [17, 19, 25, 35]. Antibiotics‐impregnated cement is sometimes used for the prevention of PJI in arthroplasties [5, 6, 22]. Recently, intrawound administration of vancomycin has been performed in various fields.…”
Section: Introductionmentioning
confidence: 99%